Implementasi Pemikiran Mukti Ali Scientific Cum Doctrinaire Terhadap Pembelajaran PAI di Madrasah - Muslim Muslim; Muqowim Muqowim; Radjasa Radjasa (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2021)
This articles discusses the implementation of Mukti Ali’s thought ‘Scientific Cum Doctrinaire in the study of Islamic Religious Education (PAI) in Madrasa. This article written based on a qualitative research approach to the type of literature review of Mukti Ali’s works in the form of books, articles, papers, magazines, and other scientific works that are relevant to the research topic. In this study, there are two sources of data, primary and secondary data sources. Primary data sources in the form of Mukti Ali’s works and secondary data source in the form of scientific work in the form of articles, papers, research reports, and other that discuss Mukti Ali’s thoughts. This study shows that the application of Mukti Ali’s ‘Scientific Cum Doctrinaire’ thinking in learning Islamic Religious Education in madrasas must be based on factual and objective data. Although in its application the scientific method does not have to be applied procedurally, bearing in mind that in PAI learning there is material which cannot be rationalized and internalized internally, such as material relating in the form of Islamic teachings, principles, and dogmas to suit religious phenomena and current scientific developments so that the understanding of Islamic religious teaching is not rigid (textual) but flexible and remains in the corridor of valid methodology.